(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
In recent years there has been a significant increase in digital advertising through influencers being active on many social media platforms. Budgets for influencer marketing rise yearly, and the return on investment from influencer marketing is higher than from other marketing channels. Therefore, influencer marketing is here to stay, and the pandemic has turned many customers online. Nowadays, customers most often collect information regarding products or services from influencers. The factors that may affect customers’ purchase decisions are seen in influencers’ credibility and advertising disclosure. A systematic literature review was done to provide an overview of the related influencer marketing field and the impact of advertising disclosure and source credibility on purchase intention. The terms ("Purchase intention") and ("influencer credibility" OR "source credibility" and “advertising disclosure”) were used to collect data. The papers were reviewed to determine how influencer credibility and advertising disclosure impact customer purchase behavior. Results indicate that influencer credibility traits positively influence purchase intention, and advertisement disclosure may impact customer purchase intention differently.